Necessity of Dividing General Methodology of Psychology into a Number of Particular Trends of Meta-Scientific Research - D A Yatsenko (Peoples' Friendship University of Russia (RUDN University), 2013)
The article states the illegitimacy of including the problems and matters not directly connected with the methods of scientific studying the psychological phenomena in the works on the methodology of psychology. It also argues about the necessity of separating such problems from the methodology of psychology and transferring them into different meta-psychological sciences: philosophy of psychology, logics of psychology, fundamental problem psychology, meta-theoretical psychology. In conclusion the problems and matters that must be posed and solved specifically in the methodology of psychology and in other meta-sciences are stated.